Profil Kompetensi Interpersonal Siswa Sekolah Menengah Pertama Di Sukabumi Pada Materi Pemanasan Global Berdasarkan Gender: (Profile of Interpersonal Competency of Junior High School Students in Sukabumi on Global Warming Materials Based on Gender) - Ayu Restu Sagita; Sistiana Sistiana; Aa Juhanda (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
Interpersonal competence is the ability to communicate in interacting with other humans to achieve certain goals. Interpersonal competence is very important for every student to have so that their abilities can develop and be well conveyed. In addition to cognitive abilities that student need to develop, interactions during adolescence are also important because without good interactions, adolescents will lose relationships with the people around them. The purpose of this study was to determine the interpersonal competence of seventh grade students in one of the schools in the city of Sukabumi on global warming material based on gender. This study used a quantitative descriptive method, with a sample of 31 students, formed into 6 groups. The instrument used was an observation sheet consisting of 10 statements developed from 5 indicators. In learning, students are formed in groups to make a simple practical video. The indicators in the instrument consist of the ability to initiate (Initiation), the ability to be assertive (Negative assertion), the ability to be open (self-disclosure), the ability to provide support to others (emotional support), and the ability to manage conflict (Conflict management). From the result of the research that has been done, the scores of all groups are quite good. The highest value is 85, the lowest value is 72,5. The greatest score per indicator is in providing support to others (Emotional support) and managing conflict (Conflict management) of 79%, while the lowest score is 73% on open indicators (self-disclosure). Based on gender, female students obtained higher interpersonal competence scroe than male students, this can be caused by several factors such as interaction with parents, education, age, environmental influences and desires of the individual, and extroverted personality. Abstrak. Kompetensi interpersonal merupakan kemampuan berkomunikasi dalam berinteraksi dengan manusia lain untuk mencapai tujuan tertentu. Kompetensi interpersonal sangat penting untuk dimiliki setiap siswa agar kemampuan yang dimilikinya dapat berkembang dan tersampaikan secara baik. Selain kemampuan kognitif yang perlu dikembangkan oleh siswa, interaksi pada masa remaja pun menjadi hal penting karena tanpa adanya interaksi yang baik, remaja akan kehilangan relasi dengan orang-orang di sekitarnya. Tujuan dari penelitian ini yaitu untuk mengetahui kompetensi interpersonal siswa kelas VII disalah satu sekolah yang ada di kota Sukabumi pada materi pemanasan global berdasarkan gender. Penelitian ini memakai metode deskriptif kuantitatif, dengan sampel sebanyak 31 siswa, dibentuk menjadi 6 kelompok. Instrumen yang digunakan berupa lembar observasi yang terdiri dari 10 pernyataan yang dikembangkan dari 5 indikator. Dalam pembelajarannya siswa dibentuk kelompok untuk membuat sebuah video praktikum sederhana. Indikator dalam instrumen terdiri dari kemampuan berinisiasi (Initiation), kemampuan bersikap asertif (Negative assertion), kemampuan bersikap terbuka (self-disclosure), kemampuan memberi dukungan kepada orang lain (Emotional support), dan kemampuan mengelola konflik (Conflict management). Dari hasil penelitian yang telah dilakukan, nilai semua kelompok cukup baik. Nilai tertinggi sebesar 85, nilai terendah sebesar 72,5. Perolehan skor per indikator yang terbesar terdapat pada memberi dukungan kepada orang lain (Emotional support) dan mengelola konflik (Conflict management) sebesar 79%, sedangkan skor terendah yaitu 73% pada indikator bersikap terbuka (Self-disclosure). Berdasarkan gender siswa perempuan memperoleh skor kompetensi interpersonal lebih tinggi daripada siswa laki-laki, ini dapat disebabkan oleh beberapa faktor seperti, interaksi dengan orang tua, pendidikan, umur, pengaruh sekeliling dan keinginan dari diri individu tersebut, dan kepribadian yang ekstrovert.